Correlative Microscopy and Nanofabrication with AFM Integrated with SEM. (November 2019) - Holz, Mathias; Reuter, Christoph; Ahmad, Ahmad; Reum, Alexander; Hofmann, Martin; Ivanov, Tzvetan; Rangelow, Ivo W.
Abstract: Abstract : This article describes an atomic force microscope (AFM) that can operate in any scanning electron microscope (SEM) or SEM combined with a focused ion-beam (FIB) column. The combination of AFM, SEM imaging, energy-dispersive X-ray spectrometry (EDX), FIB milling, and nanofabrication methods (field-emission scanning probe lithography, tip-based electron beam induced deposition, and nanomachining) provides a new tool for correlative nanofabrication and microscopy. Piezoresistive, thermo-mechanically actuated cantilevers (active cantilevers) are used for fast imaging and nanofabrication. Thus, the AFM with active cantilevers integrated into an SEM (AFMinSEM) can generate and characterize nanostructures in situ without breaking vacuum or contaminating the sample.